Analysis of epidemiology, lifestyle, and psychosocial factors in patients with back pain admitted to an orthopedic emergency unit - Gotfryd,Alberto Ofenhejm (2015)
ABSTRACT Objective: To correlate epidemiological data, lifestyle, and psychosocial factors as predictors for clinical manifestation of back pain in patients treated at the orthopedic emergency unit of a Brazilian tertiary care hospital, and to evaluate their interest in participating in a hypothetical program for physical rehabilitation. Methods: This is an observational cross-sectional study. We evaluated 210 patients from the emergency department of a tertiary hospital with a major complaint of back pain. We used: epidemiological multiple-choice questionnaires developed for this study; Oswestry questionnaire for physical disability; Hospital Anxiety and Depression Scale (HAD) scale. Data analyses were performed using SAS - Statistical Analysis System (SAS Institute, 2001). Measurements were performed with the SAS functions Proc MEANS and Proc Freq. Results: The mean age was 39.1 years and there was no predominance between genders. The usual work activity was administrative (65.2% of cases). The mean body mass index was 26.0, indicating overweight. The majority (83.3%) of patients had low physical disability (Oswestry 0 – 40%). The number of medical visits in the previous 6 months (p=0.04) and the scores of anxiety and depression (p=0.05), independently, were correlated with physical disability. Most patients (77%) would agree to participate in a hypothetical program of physical rehabilitation for prevention of back pain. Conclusion: Patients with back pain complaints were predominantly young adults, sedentary or hypoactive, overweight, and with recurrent complaints of symptoms. Most participants had low levels of physical disability and would accept participation in a hypothetical physical rehabilitation program for the prevention of back pain.